PRAKTIK POLIGAMI TANPA IZIN DI BACAN TIMUR HALMAHERA SELATAN - Coronas, Ahmad Abdullah; Sanmas, Abu; Umasugi, Nirwan; Harwis, Harwis; Abubakar, Fatum (Indonesian Journal of Shariah and Justice, 2023)
The practice of polygamy without a permit in the East Bacan District, South Halmahera Regency. This study aims to find the main issues that underlie the occurrence of the practice of polygamy without a permit in the East Bacan District, South Halmahera Regency. This study is field research. The research method used is descriptive qualitative research, namely a type of research that provides a systematic and factual description of situations and events regarding factors, characteristics and relationships between phenomena, with theoretical, normative and empirical juridical approaches. This study concluded that the implementation of polygamy without a permit in East Bacan District was carried out through cases of premarital pregnancy and coupled with low public awareness regarding the importance of marriage procedures. The limited budget and human resources owned by the East Bacan District KUA in conducting outreach to the people of East Bacan District have triggered the lack of attention from the Office of the Religious Affairs Office of Bacan District to minimize the incidence of polygamy without a permit in East Bacan District. The implementation of polygamy without a permit in East Bacan District had legal impacts, including the weak legal status of marriage, the absence of birth certificates for children born in polygamous marriages without permission.